EEG Oscillations Reveal Neural Correlates of Evidence Accumulation - van Vugt, Marieke K.; Simen, Patrick; Nystrom, Leigh E.; Holmes, Philip; Cohen, Jonathan D. (Frontiers in Neuroscience, 2012)
Recent studies have begun to elucidate the neural correlates of evidence accumulation in perceptual decision making, but few of them have used a combined modeling-electrophysiological approach to studying evidence accumulation. We introduce a multivariate approach to EEG analysis with which we can perform a comprehensive search for the neural correlate of dynamics predicted by accumulator models. We show that the dynamics of evidence accumulation are most strongly correlated with ramping of oscillatory power in the 4-9 Hz theta band over the course of a trial, although it also correlates with oscillatory power in other frequency bands. The rate of power decrease in the theta band correlates with individual differences in the parameters of drift diffusion models fitted to individuals' behavioral data.